Family-Reported Experiences Evaluation (FREE) study: a mixed-methods study to evaluate families' satisfaction with adult critical care services in the NHS - Stephen E Wright; Emma Walmsley; Sheila E Harvey; Emily Robinson; Paloma Ferrando-Vivas; David A Harrison; Ruth R Canter; Elaine McColl; Annette Richardson; Michael Richardson; Lisa Hinton; Daren K Heyland; et al. (National Institute for Health Research, 2015)
Background: To improve care it is necessary to feed back experiences of those receiving care. Of patients admitted to intensive care units (ICUs), approximately one-quarter die, and few survivors recollect their experiences, so family members have a vital role. The most widely validated tool to seek their views is the Family Satisfaction in the Intensive Care Unit questionnaire (FS-ICU). Objectives: To test face and content validity and comprehensibility of the FS-ICU (phase 1). To establish internal consistency, construct validity and reliability of the FS-ICU; to describe family satisfaction and explore how it varies by family member, patient, unit/hospital and other contextual factors and by country; and to model approaches to sampling for future use in quality improvement (phase 2). Design: Mixed methods: qualitative study (phase 1) and cohort study (phase 2). Setting: NHS ICUs (n = 2, phase 1; n = 20, phase 2). Participants: Health-care professionals, ex-patients, family members of ICU patients (n = 41, phase 1). Family members of ICU patients (n = 12,303, phase 2). Interventions: None. Main outcome measures: Key themes regarding each item of the 24-item FS-ICU (FS-ICU-24) (phase 1). Overall family satisfaction and domain scores of the FS-ICU-24 (phase 2). Results: In phase 1, face validity, content validity and comprehensibility were good. Adaptation to the UK required only minor edits. In phase 2, one to four family members were recruited for 60.6% of 10,530 patients (staying in ICU for 24 hours or more). Of 12,303 family members, 7173 (58.3%) completed the questionnaire. Psychometric assessment of the questionnaire established high internal consistency and criterion validity. Exploratory factor analysis indicated new domains: satisfaction with care, satisfaction with information and satisfaction with the decision-making process. All scores were high with skewed distributions towards more positive scores. For family members of ICU survivors, factors associated with increased/decreased satisfaction were age, ethnicity, relationship to patient, and visit frequency, and patient factors were acute severity of illness and invasive ventilation. For family members of ICU non-survivors, average satisfaction was higher but no family member factors were associated with increased/decreased satisfaction; patient factors were age, acute severity of illness and duration of stay. Neither ICU/hospital factors nor seasonality were associated. Funnel plots confirmed significant variation in family satisfaction across ICUs. Adjusting for family member and patient characteristics reduced variation, resulting in fewer ICUs identified as potential outliers. Simulations suggested that family satisfaction surveys using short recruitment windows can produce relatively unbiased estimates of average family satisfaction. Conclusions: The Family-Reported Experiences Evaluation study has provided a UK-adapted, psychometrically valid questionnaire for overall family satisfaction and three domains. The large sample size allowed for robust multilevel multivariable modelling of factors associated with family satisfaction to inform important adjustment of any future evaluation. Limitations: Responses to three free-text questions indicate the questionnaire may not be sensitive to all aspects of family satisfaction. Future work: Reservations remain about the current questionnaire. While formal analysis of the free-text questions did not form part of this proposal, brief analysis suggested considerable scope for improvement of the FS-ICU-24. Study registration: Current Controlled Trials ISRCTN47363549. Funding details: The National Institute for Health Research Health Services and Delivery Research programme.